Music education and social projects: discussing the relationship between music, belonging, and social demands in two countries - Elisama da Silva Gonçalves Santos; Anderson Brasil (Universidade Federal do Norte do Tocantins, 2021)
The social projects in music are a modern topic in the field of music education. Due to the importance of the point provided here, it is indicated the expansion of the object learning and teaching music beyond the aspects of social context in which these music social projects are inserted. Therefore, we seek to achieve an expanded look at the musical experiences offered in social projects not only in Brazil, but also in contexts with refugees originally from countries at war. In this article, we also illustrate experiences in social projects located in North Dakota, in the United States. Through dialogues with researchers of music education, we seek to reflect on the situation of refugees from countries at war, the sense of belonging, and the role of music education in communities in relation to the demands that permeate the musical aspects.